Heart rate variability in patients with stable angina pectoris as a risk factor for adverse clinical prognosis: relationship with affective depressive symptoms - A. O. Lobe; A. I. Chebotova; D. N. Ivanchenko; N. P. Dorofeeva; A. S. Pleskachev; E. Yu. Radchenko; S. V. Shlyk (Медицинский вестник Юга России, 2020)
Objective: to investigate the heart rate variability (HRV) parameters of patients with a stable angina pectoris depending of presence depressive disorders; to identify the influence of affective symptoms on the clinical outcome during 12 months of observation.Material and methods: there are 121 male patients included in research with a stable angina pectoris II – III functional classes, hospitalized for a drug treatment and planned percutaneous coronary intervention (PCI) with stenting. The severity of affective symptoms and HRV are being assessed.Results: patients with depressive symptoms in the conservative treatment group had low SDNN level; patients with psychoemotional disorders in the surgical treatment group had differences by all HRV parameters (SDNN, SDANN, SDNN, rMSSD pNN50). Clinically unfavorable outcome, including intermediate points such as increase in angina attacks, re-hospitalization, stent’s restenosis, were mostly registered during 12 months of observation in the groups with affective symptoms.Conclusions: presence of depressive symptoms of patients with stable angina pectoris is accompanied with low HRV parameters, which is connected with worsening of cardiac prognosis.